Respuesta :

Answer:

(gof) (4) = 9

Hence, option A is true.

Step-by-step explanation:

f(x)=-x³

g(x)=|1/8x -1|

(gof) (4) = g{f(4)}

First wee need to determine f(4)

f(4)=-(4)³

    = -64

so

  (gof) (4) = g{f(4)} = g(-64)

                             =  [tex]\left|\frac{1}{8}\left(-64\right)-1\right|[/tex]

                             [tex]=\left|-\frac{1}{8}\cdot \:64-1\right|[/tex]

                             [tex]=\left|-8-1\right|[/tex]

                             [tex]=\left|-9\right|[/tex]

[tex]\mathrm{Apply\:absolute\:rule}:\quad \left|-a\right|=a[/tex]

                             [tex]=9[/tex]        

Thus,

(gof) (4) = 9

Hence, option A is true.